ASOSIASI KARAKTERISTIK CEO TERHADAP POTENSI KESULITAN KEUANGAN PERUSAHAAN - Tanjaya, Felix Leonardo; Santoso, Eko Budi (Media Akuntansi dan Perpajakan Indonesia, 2020)
This study aims to determine the effect of CEO characteristics in terms of facial masculinity, education, and experience to potential of financial distress. Facial masculinity was measured using dummy variables consisting of masculinity and feminism. Education was measured using dummy variables of educational level; meanwhile, experience was measured using dummy variables from CEO work experience. This research used quantitative with secondary data types taken from annual reports of non-financial companies that are listed on Indonesia Stock Exchange. The sampling method used purposive sampling with the observation period of 2016–2018 and obtained a total sample of 259 samples. The method data analysis used multiple linear regression analysis. The result showed that: (1) CEO face masculinity did not affect financial distress, (2) CEO education did not affect financial distress, (3) CEO experience positively influenced financial distress. The results showed the fact that CEO experience is an important factor that could improved company performance for avoiding financial distress potential.